Polyamide Zeolitic Imidazolate Framework 8 Polysulfone Thin Film Nanocomposite Membrane For The Treatment Of Produced Water Via Forward Osmosis - Beh, Jyh Jiunn (2019)
Produced water treatment using forward osmosis (FO) membrane has faced challenges such as high volume of wastewater and poor membrane chemical stability against produced water. Hence, a polyamide/zeolitic imidazolate framework-8 (ZIF-8) thin film nanocomposite (TFN) membrane with improved water permeability and chemical stability was developed in this work. Nanosized ZIF-8 particles with unimodal size distribution were successfully synthesized at low reaction temperature (5 °C) by using high zinc ion (0.20 M) and 2-methylimidazole (1.60 M) concentrations. Poly(sodium 4-styrenesulfonate) (PSS) coating was found to stabilize the ZIF-8 particles against dissolution in water, which enabled them to be dosed in via aqueous phase during interfacial polymerization. Concurrently, a thin film composite (TFC) membrane with high NaCl selectivity was synthesized by forming polyamide film above a polysulfone (PSf) support membrane via interfacial polymerization. The polyamide film prepared at 3 w/v% m-phenylenediamine concentration, 0.10 w/v% trimesoyl chloride concentration and 60 s reaction duration was thin and dense. It achieved high NaCl selectivity of 0.673 bar-1 as characterized via reverse osmosis filtration test. This TFC membrane was further refined by adjusting PSf/ polyvinylpyrrolidone (PVP) ratio and using co-solvent in preparing the polymer dope to improve support membrane surface wettability and polyamide film formation above it. The support membrane prepared at PSf/PVP ratio of 0.941 without co-solvent had a surface with good wettability, regular pore size and moderate roughness (52.9 nm). This improved the TFC membrane NaCl selectivity to 0.691 bar-1 compared to that prepared on PSf support membrane without polymer dope modification. The support and reaction conditions of this TFC membrane were combined with the PSS-coated ZIF-8 particles to develop the TFN membrane. The pure water permeability of TFN membrane synthesized with triethylamine (TEA) (2.506 L/m2∙h∙bar) improved significantly over that of both TFC membrane (1.110 L/m2∙h∙bar) and TFN membrane synthesized without TEA (1.159 L/m2∙h∙bar). The enhanced water transport of TFN membrane was further manifested by its higher water flux relative to TFC membrane in filtering both synthetic and real produced water with oil concentration of 500 and 377.8 ppm respectively using FO process. Moreover, due to the chemically stable ZIF-8 particles against hydrocarbons, the TFN membrane demonstrated improved swelling resistance and chemical stability against produced water than the TFC membrane. In conclusion, this work successfully developed a polyamide/ZIF-8 TFN membrane with high water permeability, good chemical stability against produced water and high oil rejection of more than 99 % for produced water treatment using FO process.